2017
DOI: 10.1371/journal.pone.0178839
|View full text |Cite
|
Sign up to set email alerts
|

Admixture mapping of pelvic organ prolapse in African Americans from the Women’s Health Initiative Hormone Therapy trial

Abstract: Evidence suggests European American (EA) women have two- to five-fold increased odds of having pelvic organ prolapse (POP) when compared with African American (AA) women. However, the role of genetic ancestry in relation to POP risk is not clear. Here we evaluate the association between genetic ancestry and POP in AA women from the Women’s Health Initiative Hormone Therapy trial. Women with grade 1 or higher classification, and grade 2 or higher classification for uterine prolapse, cystocele or rectocele at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…A related approach involves a Bonferroni correction on the estimated effective number of independent tests; 13,19,31,32 however, a number of authors [33][34][35] have suggested that this approach does not always guarantee family-wise error rate control in genome-wide association studies. Permutation-based 22,24,36,37 and simulation-based 20,38,39 multiple testing correction procedures are often considered to be the gold standard for genetic association studies but can be very computationally intensive. Alternatives to these procedures, based on the multivariate normal distribution, have been suggested to speed up computation time.…”
Section: Introductionmentioning
confidence: 99%
“…A related approach involves a Bonferroni correction on the estimated effective number of independent tests; 13,19,31,32 however, a number of authors [33][34][35] have suggested that this approach does not always guarantee family-wise error rate control in genome-wide association studies. Permutation-based 22,24,36,37 and simulation-based 20,38,39 multiple testing correction procedures are often considered to be the gold standard for genetic association studies but can be very computationally intensive. Alternatives to these procedures, based on the multivariate normal distribution, have been suggested to speed up computation time.…”
Section: Introductionmentioning
confidence: 99%
“…Pada suatu studi Women's Health Initiative (WHI) di Amerika menunjukkan sebanyak 40% wanita mengalami POP setelah menopause dengan 20% wanita dilakukan operasi pada usia 80 tahun. 1,2 Menurut laporan tahunan Rumah Sakit Dr. Hasan Sadikin Bandung didapatkan prevalensi prolapsus organ panggul sebesar 20%, sedangkan penelitian di Rumah Sakit Dr. Moewardi Surakarta dari tahun 2013-2015 didapatkan 258 pasien dengan prolapsus uteri. 3 Faktor risiko terjadinya POP bersifat multifaktorial antara lain paritas, persalinan pervaginam, usia, obesitas, kelainan jaringan ikat, status menopause, dan konstipasi kronis yang menyebabkan kelemahan pada otot dasar panggul.…”
Section: Pendahuluanunclassified